(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the association and discriminative performance of the Pneumonia Severity Index (PSI) for 30-day mortality in older adults hospitalized with community-acquired pneumonia. Methods: A prospective cohort study was conducted on 126 patients aged ≥60 years with community-acquired pneumonia admitted to the Geriatrics Department of Da Nang Hospital between March and August 2025. PSI was calculated within the first 24 hours of admission. The association between PSI and 30-day mortality was assessed using logistic regression. Discriminative performance was evaluated using the area under the receiver operating characteristic curve (AUC). Results: The mean age was 80.9 ± 10.2 years, and most patients were classified as PSI class IV–V. The 30-day mortality rate was 14.3%. Each 10-point increase in PSI was associated with a 1.16-fold increase in the odds of death (OR = 1.16; 95% CI: 0.99–1.34; p = 0.062). The overall AUC of PSI was 0.624 (95% CI: 0.474–0.770; p = 0.108), indicating limited discriminative ability. In patients aged ≥80 years, the AUC reached 0.718 (p = 0.031); however, the difference between age groups was not statistically significant. Conclusions: PSI showed a trend toward association with 30-day mortality; however, its discriminative ability was limited in this geriatric cohort. While PSI may still be useful for initial risk stratification, its prognostic value may be improved by incorporating comprehensive geriatric assessment.